Dinuclear salen cobalt complex incorporating Y(OTf)(3): enhanced enantioselectivity in the hydrolytic kinetic resolution of epoxides - Patel, Deepak; Kurrey, Ganesh Ram; Shinde, Sandip S.; Kumar, Pradeep; Kim, Geon-Joong; Thakur, Santosh Singh (RSC Advances, 2015)
The activation of inactive Jacobsen's chiral salen Co(II) (salen = N,N'-bis(3,5-di-tert-butylsalicylidene)-1,2-cyclohexanediamine) compound is attained by dinuclear chiral salen Co(III)-OTf complex formation with yttrium triflate. The yttrium metal not only displays a promoting effect on electron transfer, but also assists in forming two stereocentres of a Lewis acid complex with Co(III)-OTf. We found that the binuclear Co-complex significantly enhanced reactivity and enantioselectivity in the hydrolytic kinetic resolution of terminal epoxides compared to its analogous monomer and kinetic data are also consistent with these results.

Sucrose capped gold nanoparticles as a plasmonic chemical sensor based on non-covalent interactions: application for selective detection of vitamins B-1 and B-6 in brown and white rice food samples - Shrivas, Kamlesh; Nirmalkar, Nidhi; Thakur, Santosh Singh; Deb, Manas Kanti; Shinde, Sandip S.; Shankar, Ravi (Food Chemistry, 2018)
We report simple and selective method for detection of vitamins B-1 and B-6 in brown and white rice samples using localized surface plasmon resonance (LSPR) of sucrose capped gold nanoparticles (AuNPs) as a chemical sensor colorimetrically. Here, detection is based on the color change of AuNPs from pink to blue followed by a red shift of LSPR absorption band in UV-vis region with the addition of vitamins B-1 and B-6 into the NPs solution. A good linear range was observed in the range of 25-1000 ngmL(-1) with detection limit of 8 ngmL(-1) for B-1 and 50-1000 ngmL(-1) with detection limit of 15 ngmL(-1) for vitamins B-6. The employment of AuNPs for detection of B-1 and B-6 vitamins in rice food samples showed remarkable abilities in terms of the simplicity, low cost, stability, reproducibility and sensitivity.